First comparative characterization of three distinct ferritin subunits from a teleost : Evidence for immune-responsive mRNA expression and iron depriving activity of seahorse (Hippocampus abdominalis) ferritins - Oh, M.; Umasuthan, N.; Elvitigala, D. A. S; Wan, Q.; Jo, E.; Noh, G.E.; Shin, S.; Rho, S.; Lee, J. (Elsevier, 2016)
Ferritins play an indispensable role in iron homeostasis through their iron-withholding function in living beings. In the current study, cDNA sequences of three distinct ferritin subunits, including a ferritin H, a ferritin M, and a ferritin L, were identified from big belly seahorse, Hippocampus abdominalis, and molecularly characterized. Complete coding sequences (CDS) of seahorse ferritin H (HaFerH), ferritin M (HaFerM), and ferritin L (HaFerL) subunits were comprised of 531, 528, and 522 base pairs (bp), respectively, which encode polypeptides of 177, 176, and 174 amino acids, respectively, with molecular masses of ~20e21 kDa. Our in silico analyses demonstrate that these three ferritin subunits exhibit the typical characteristics of ferritin superfamily members including iron regulatory elements, domain signatures, and reactive centers. The coding sequences of HaFerH, M, and L were cloned and the corresponding proteins were overexpressed in a bacterial system. Recombinantly expressed HaFer proteins demonstrated detectable in vivo iron sequestrating (ferroxidase) activity, consistent with their putative iron binding capability. Quantification of the basal expression of these three HaFer sequences in selected tissues demonstrated a gene-specific ubiquitous spatial distribution pattern, with abundance of mRNA in HaFerM in the liver and predominant expression of HaFerH and HaFerL in blood. Interestingly, the basal expression of all three ferritin genes was found to be significantly modulated against pathogenic stress mounted by lipopolysaccharides (LPS), poly I:C, Streptococcus iniae, and Edwardsiella tarda. Collectively, our findings suggest that the three HaFer subunits may be involved in iron (II) homeostasis in big belly seahorse and that they are important in its host defense mechanisms
Keywords: Big belly seahorse; Ferritin H, L, and M subunits; Tissue mRNA expression; Immune response Iron (II) chelation/withholding